Analysis of Optimum Marketing Strategy with Game Theory (Case Study: Marketplace Indonesian - Nabila Sari, Anastasya; Aryanny, Enny (Aptisi Transactions On Technopreneurship (ATT), 2022)
The increasing number of pandemic cases in early 2021, has made online trading (marketplace) more widespread, making competition for marketplace companies getting tighter. Marketing strategy competition can be tested with a game theory approach. This study aims to determine the optimum marketing strategy in the marketplace so as to increase market share. From the data processing on the payoff matrix, there is no saddle point where the maximum value is not the same as the minimum value so that the pure strategy is not the optimum strategy. Furthermore, the data is processed using the POM-QM program to determine the value of the most optimum marketing strategy for each marketplace. Get games between marketplaces using a mixed strategy. In the Shopee and Tokopedia games, the optimal game value is 9%. In the second game, Shopee and Lazada, the optimal game value is 10%. In Shopee and Bukalapak games, the optimal game value is 8%. In the Shopee and Blibli games, the optimal game value is 16%. In the Tokopedia and Lazada games, the optimal game value is 10%. In the Tokopedia and Bukalapak games, the optimal game value is 9%. In the Tokopedia and Blibli games, the optimal game value is 9%. In the Lazada and Bukalapak games, the optimal game value is 11%. In the Lazada and Blibli games, the optimal game value is 13%. In the last game, Bukalapak and Blibli, the optimal game value was 14%.